Efektifitas Teknik Relaksasi Otot Progresif Terhadap Intensitas Nyeri Akut Pascaoperasi Fraktur Tulang Panjang - Syah Fara Dillasani Sirait; Dudut Tanjung; Dedi Ardinata; Tasrif Hamdi; Nur Asnah Sitohang (Jurnal Ners, 2026)
Abstract Acute postoperative pain following long bone fractures is a common clinical problem that may hinder the healing process and delay early patient mobilization. This study aimed to analyze the effectiveness of Progressive Muscle Relaxation (PMR) techniques in reducing the intensity of acute postoperative pain in patients with long bone fractures. A randomized controlled trial with a pretest–posttest control group design was employed. The sample consisted of 72 respondents, who were divided into an intervention group (NSAIDs + PMR) and a control group (NSAIDs only). Univariate analysis showed that the mean pain intensity in the intervention group decreased from 68.2 ± 8.5 mm before the intervention to 32.4 ± 7.6 mm after the intervention, while in the control group, mean pain intensity decreased from 67.9 ± 8.1 mm to 48.6 ± 8.9 mm. Bivariate analysis using the paired t-test demonstrated a statistically significant reduction in pain intensity before and after treatment in both the intervention group (p = 0.000) and the control group (p = 0.001). Furthermore, the independent t-test revealed a significant difference in post-intervention pain intensity between the intervention and control groups (p = 0.000). These findings indicate that Progressive Muscle Relaxation is effective as a complementary therapy in reducing acute postoperative pain following long bone fractures and is recommended for integration into postoperative nursing care. Keywords: Progressive Muscle Relaxation Technique, acute pain, long bone fracture, postoperative, NSAID